HUBUNGAN ANTARA ASUPAN ASAM LEMAK TRANS DENGAN PERSEN LEMAK TUBUH DAN STATUS GIZI PADA ORANG DEWASA DI KABUPATEN DAN KOTA BOGOR - Zaenudin Zaenudin; Mira Dewi; Yekti Hartati Effendi (Jurnal Gizi dan Pangan, 2012)
The objective of this study was to determine relationship between trans fatty acid intake with percentage of body fat and nutritional status among adults in Bogor rural and urban area. The research was conducted using a cross sectional study. The number of subjects for each region was 48 adults aged 20—65 years which selected purposively. The results showed that most of subjects in urban and rural areas were in categorized as high deficient of energy (<70% RDA), i.e. 29.17% and 33.33%, respectively. The percentage of fat adequacy was 43.75% in rural area, which was categorized as sufficient, and 45.83% in urban area, which was categorized as high. Meanwhile, most of the subjects (97.92%) in both areas had adequacy level of trans fatty acid intake as recommended. Body fat percentage in subjects was 24.81±8.44 in rural area and 27.62±801 in urban area. In the meanwhile, 58.30% of subjects in rural and 64.4% of subjects in urban areas had normal nutritional status. There was no significant difference (p>0.05) between trans fatty acid intake, adequacy level intakes of energy, total fat, trans fatty acid, and body fat percentage. However there was a significant difference between nutritional status of subjects in rural and urban areas (p<0.05). There was no relationship between adequacy level intakes of energy, total fat, and trans fatty acid, with body fat percentage and nutritional status (p>0.05), but there was significant correlation between body fat percentages and nutritional status of subjects (p<0.05).